2023
DOI: 10.12688/gatesopenres.14375.1
|View full text |Cite
|
Sign up to set email alerts
|

The economic costs of malaria in pregnancy: evidence from four sub-Saharan countries

Abstract: Background Malaria in pregnancy is a major public health problem in sub-Saharan Africa (SSA), which imposes a significant economic burden. We provide evidence on the costs of malaria care in pregnancy to households and the health system in four high-burden countries in SSA.  Methods Household and health system economic costs associated with malaria control in pregnancy were estimated in selected areas of the Democratic Republic of Congo (DRC), Madagascar (MDG), Mozambique (MOZ) and Nigeria (NGA). An exit surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…(37) According to other study, spatial repellents (SR) can either completely stop or significantly limit the transmission of malaria. (15,38) Consistent with the findings of a previous study that looked at housing and malaria, the condition of the in-house wall was shown in this study to be a protective factor against malaria in the study region. Good house design in Uganda decreased the danger of malaria by preventing mosquito vectors from entering the country.…”
Section: Health Dynamicssupporting
confidence: 91%
See 1 more Smart Citation
“…(37) According to other study, spatial repellents (SR) can either completely stop or significantly limit the transmission of malaria. (15,38) Consistent with the findings of a previous study that looked at housing and malaria, the condition of the in-house wall was shown in this study to be a protective factor against malaria in the study region. Good house design in Uganda decreased the danger of malaria by preventing mosquito vectors from entering the country.…”
Section: Health Dynamicssupporting
confidence: 91%
“…For instance, there is a chance that sand miners in Tanjeh and Brufut, The Gambia, would get malaria. (14,15) Additional research has demonstrated that mining regions are more susceptible to malaria, with persistent evidence of malaria vectors flourishing there, as observed in the West Kenyan highlands. (4,16) Changes in land use can have an influence on the spread of malaria, and socioeconomic and behavioural variables are among the risk factors for malaria in mining regions.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was conducted from the perspective of the health system; however, the incremental net costs and ICERs would be further reduced if households’ cost savings resulting from averted episodes of maternal malaria were considered. Details on the economic burden of malaria on households in project areas have been analysed and discussed elsewhere 37…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the number of clinical malaria episodes during pregnancy by using self-reported data from pregnant women in intervention areas 37. While not ideal due to its susceptibility to bias, this approximation is unlikely to affect the CE substantially since the surrogate measure of clinical malaria contributed less than 5% to the total DALYs averted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation